Optimal placement of wind turbine in a radial distribution network using PSO method - Yahiaoui Merzoug; Bouanane Abdelkrim; Boumediene Larbi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
The aim of this article is to apply the Particle Swarm Optimization (PSO) method to find the best location for the wind turbine in the radial distribution network. The optimal location is found using the loss sensitivity factor. By respecting the constraints of the active power transmitted in the branches and the limits of the voltages modules for all the nodes. The validity of this method is tested on a 33-IEEE test network and the results obtained are compared with the results of basic load flow.